Quantitative Physiology Approaches to Understand and Optimize Reducing Power Availability in Environmental Bacteria - Nikel Mayer, Pablo Iván (2015)
The understanding of how carbon fluxes are distributed through a metabolic network offers an overview of the pathways that a given microorganism uses to produce energy, reducing power, and biomass. These invaluable data are related to the physiological state of the cell and provide information about the metabolic potential of microorganisms for specific environmental and biotechnological applications such as the degradation of toxic compounds (e.g., hydrocarbons) or the targeted production of high value-added products (e.g., lipids). Here, we propose a general approach to explore the pathways involved in NADPH balance in bacteria, which are in turn responsible for maintaining redox homeostasis and endowing the microorganism with the ability to counteract oxidative stress. We focus on the fluxes catalyzed by NADP+-dependent enzymes in the metabolic network of the model soil bacterium Pseudomonas putida KT2440. This environmental microorganism is a promising cell factory for a number of NADPH-dependent biotransformations, including industrial and bioremediation processes. The relevant enzymes involved in redox balance in strain KT2440 are (1) glucose-6-phosphate dehydrogenase, (2) 6-phosphogluconate dehydrogenase, (3) isocitrate dehydrogenase, (4) malic enzyme, and (5) 2-keto-6-phosphogluconate reductase. NADPH can be generated or consumed by other enzymatic reactions depending on the microorganism; however, the first four enzymes listed above are recognized as a major source of reducing power in a wide variety of microorganisms. The present protocol includes a first stage in which the NADPH balance is derived from fluxomic data and in vitro enzymatic assays. A second step is then proposed, where the redox ratios of pyridine dinucleotides and the cell capacity to counter oxidative stress are qualitatively correlated.